Pengaruh WLB, Beban Kerja, Dan Karakteristik Individu Terhadap Kinerja Pegawai Pada Dinas PUPR Kota Padang - Teguh julio; Novri yendra (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to analyze the influence of work-life balance, workload, and individual characteristics on employee performance at the Public Works and Spatial Planning Office (PUPR) of Padang City. The method used is descriptive quantitative with a population of 120 employees and a sample of 120 respondents. The sampling technique was conducted in stages using purposive sampling, with the criteria being active employees at the PUPR Office of Padang City. Data analysis was conducted using multiple linear regression with the help of SPSS. The research results show that: (1) Work-life balance has a negative impact on employee performance at the PUPR Office of Padang City, where the balance between work and personal life actually reduces employees' focus and productivity in carrying out their duties, (2) Workload has a positive and significant impact on employee performance at the Dinas PUPR Kota Padang, where an increase in workload managed optimally can enhance motivation and work efficiency. (3) Individual characteristics have a positive and significant impact on employee performance at the Dinas PUPR Kota Padang, indicating that individual factors play an important role in determining work effectiveness. (4) Work-life balance, workload, and individual characteristics simultaneously have a significant impact on employee performance at the Dinas PUPR Kota Padang. It is expected that employees can adjust the balance between work and personal life without sacrificing productivity, management can manage the workload more effectively, and individual characteristics can be considered in employee development. In addition, the relevant agencies need to provide flexible policies while still encouraging optimal employee performance.